Ozonolysis combined with ultrasound as a pretreatment of sugarcane bagasse: Effect on the enzymatic saccharification and the physical and chemical characteristics of the substrate - Perrone, Olavo Micali [UNESP]; Colombari, Felippe Mariano [UNESP]; Rossi, Jessika Souza [UNESP]; Moretti, Marcia Maria Souza [UNESP]; Bordignon, Sidnei Emilio [UNESP]; Nunes, Christiane da Costa Carreira [UNESP]; Gomes, Eleni [UNESP]; Boscolo, Mauricio [UNESP]; Da-Silva, Roberto [UNESP] (Elsevier, 2016)
Sugarcane bagasse (SCB) was treated in three stages using ozone oxidation (O), washing in an alkaline medium (B) and ultrasonic irradiation (U). The impact of each pretreatment stage on the physical structure of the SCB was evaluated by its chemical composition, using an infrared technique (FTIR-ATR), and using thermogravimetric analysis (TGA/DTG). The pretreatment sequence O, B, U provided a significant reduction of lignin and hemicellulose, which was confirmed by changes in the absorption bands corresponding to these compounds, when observed using infrared. Thermogravimetric analysis confirmed an increased thermal stability in the treated sample due to the removal of hemicellulose and extractives during the pretreatment. This pretreatment released 391 mg glucose/g from treated SCB after the enzymatic hydrolysis, corresponding to a yield of 94% of the cellulose available.
Keywords: Enzyme hydrolysis; Ozonolysis; Sugarcane pretreatment; Ultrasound